First record of Ligia oceanica (Linnaeus, 1767) (Isopoda: Ligiidae) in the Canary Islands - Ramírez, Rubén (2013)
This study presents the first record of L. oceanica in the Canary Islands. Additionally, body features between L. oceanica and Ligia italica Fabricius, 1798, the other sea-slater inhabiting the Archipelago, were compared.